2011
DOI: 10.1111/j.1471-4159.2011.07185.x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary adenylate cyclase-activating polypeptide protects astroglial cells against oxidative stress-induced apoptosis

Abstract: J. Neurochem. (2011) 117, 403–411. Abstract Oxidative stress, associated with a variety of disorders including neurodegenerative diseases, results from accumulation of reactive oxygen species (ROS). Oxidative stress is not only responsible for neuron apoptosis, but can also provoke astroglial cell death. Numerous studies indicate that pituitary adenylate cyclase‐activating polypeptide (PACAP) promotes neuron survival, but nothing is known regarding the action of PACAP on astroglial cell survival. Thus, the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 47 publications
2
46
0
Order By: Relevance
“…Here, we observed that the AC inhibitor ddA blocked the inhibitory effect of ODN on H 2 O 2 -induced intracellular ROS accumulation, while the PLC inhibitor U73122 had no effect. These data are in agreement with evidences indicating that activation of the AC/PKA transduction pathway contributes to reduce the cellular ROS levels and to protect cells against oxidative stress in hippocampal cultured neurons [7] and in cultured astrocytes [5,24,31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here, we observed that the AC inhibitor ddA blocked the inhibitory effect of ODN on H 2 O 2 -induced intracellular ROS accumulation, while the PLC inhibitor U73122 had no effect. These data are in agreement with evidences indicating that activation of the AC/PKA transduction pathway contributes to reduce the cellular ROS levels and to protect cells against oxidative stress in hippocampal cultured neurons [7] and in cultured astrocytes [5,24,31].…”
Section: Discussionsupporting
confidence: 92%
“…Astroglial cells contain high levels of ROS scavenger molecules and antioxidant enzymes which play a prominent role in the protection of neurons against oxidative stress and associated cell death [4]. Nevertheless, it has recently been reported that astrocyte functionality and viability may be compromised under excessive oxidative stress conditions [12,30,31] and astrocyte apoptosis has been observed in brain injuries caused by trauma or ischemia [8,36]. Therefore, in many pathological conditions, protection of astrocytes from oxidative insult appears essential to prevent neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In diabetic nephropathy, Banki et al [ 40 ] showed that PACAP treatment increased glutathione levels. PACAP also stimulated glutathione formation, and blocked H 2 O 2 -evoked reactive oxygen species (ROS) accumulation and glutathione content reduction in oxidative stressinduced astroglial injury [ 44 ]. In kidney ischemia-reperfusion, similar changes were observed: PACAP treatment decreased MDA levels while increased GSH levels [ 45 ].…”
Section: Effects Of Exogenous Pacap In Small Bowel Ischemia-reperfusimentioning
confidence: 83%
“…Secondary cultures of rat cortical astrocytes were prepared from 1- or 2-day-old Wistar rats of both sexes as previously described (34). Briefly, cerebral hemispheres were dissected, meninges removed, and tissues collected in DMEM/Ham F12 (2:1; v/v) culture medium supplemented with 2 mM glutamine, 1‰ insulin, 5 mM HEPES, 0.4% glucose (final concentration of glucose in culture media is 4.5 g/L), and 1% of the antibiotic-antimycotic solution.…”
Section: Animals and Methodsmentioning
confidence: 99%